The ASTRI Mini-Array Gamma-Ray Experiment - Pareschi Giovanni (EPJ Web of Conferences)
The ASTRI Mini–Array is currently being installed in Tenerife at the Observatorio del Teide to explore the gamma-ray sky in the 1-100 TeV energy range with unmatched angular resolution (a few arcminutes) across a wide field of view (10.5°). The array consists of nine IACTs (Imaging Atmospheric Cherenkov Telescopes), each equipped with a 4-meter diameter dual-mirror system featuring a Schwarzschild-Couder-like optical configuration, functioning as an aplanatic system, and an innovative compact camera that utilizes SiPM (Silicon PhotoMultipliers) sensors. This paper provides a short overview of the ASTRI Mini–Array project regarding its layout, the technologies utilized, and the scientific objectives.